2008
DOI: 10.4238/vol7-2gmr399
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical alterations due to polyploidy in cassava, Manihot esculenta Crantz

Abstract: AbStRACt. Information on anatomical structure is needed by breeders working on improvement for drought tolerance. For studying the effect of polyploidy on cassava anatomy and its significance to tolerance to drought, we induced a polyploidy type of a selected clone (UnB 530) by applying an aqueous solution of 0.2% colchicine on lateral buds for a period of 12 h. The stem identified as tetraploid was propagated to produce the whole plant. Free-hand cross-sections of the median portion between stem internodes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 20 publications
3
26
1
3
Order By: Relevance
“…It is mainly consumed by low-income people as a staple food source in Africa and the Americas, and includes 99 species (Nassar, 2002). Studies of the vegetative and reproductive anatomical characteristics of Manihot have been conducted in the last decade, and have focused on the stem (Graciano-Ribeiro et al, 2009;Nassar et al, 2008Nassar et al, , 2010a, root (Bomfim et al, 2011a,b), egg cell (Hashimoto-Freitas and Nassar, 2013), and leaves (França et al, 2010). However, knowledge of Manihot petiole anatomy is limited.…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly consumed by low-income people as a staple food source in Africa and the Americas, and includes 99 species (Nassar, 2002). Studies of the vegetative and reproductive anatomical characteristics of Manihot have been conducted in the last decade, and have focused on the stem (Graciano-Ribeiro et al, 2009;Nassar et al, 2008Nassar et al, , 2010a, root (Bomfim et al, 2011a,b), egg cell (Hashimoto-Freitas and Nassar, 2013), and leaves (França et al, 2010). However, knowledge of Manihot petiole anatomy is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Metcalfe and Chalk (1983) listed some genera of Euphorbiaceae that possess internal phloem, but Manihot was not included. There have been very few anatomical studies on this genus (Graciano-Ribeiro et al, 2008;Nassar et al, 2008b). We examined the anatomy of vascular bundles in Manihot because of its potential importance in the development of droughtresistant varieties.…”
Section: Introductionmentioning
confidence: 99%
“…A genetic alteration due to colchicine treatment was reported by Nassar et al (2008) who studied anatomical alterations in the cassava plant. They found that the tetraploid type showed more prismatic and druse crystals in the cortical parenchyma, and its pericycle fibers had thicker walls.…”
Section: Discussionmentioning
confidence: 94%